ANALISIS PERAN GOOD CORPORATE GOVERNANCE (GCG) DALAM MENINGKATKAN COMPANY BUSINESS PROGRESS DAN RISK MANAGEMENT (Studi Kasus Pada BMT Agam Madani Nagari Kapau) - Selma Octaliana; Novera Martilova (Jurnal Ekonomi dan Bisnis, 2025)
The problem in this thesis occurred because there were still financing problems in the last five years at BMT Agam Madani nagari Kapau. This research uses a descriptive research method using a qualitative approach. the location of the research to be carried out is at BMT Agam Madani Nagari kapau. the data sources used are primary data sources obtained directly from informants by interviewing and secondary data sources using data in the form of documents, brochures, websites, profiles and organizational structures at BMT Agam Madani Nagari Kapau. Based on research conducted by researchers, the implementation of GCG runs efficiently in increasing company business progress. This is proven by the increasing number of customers at BMT Agam Madani Nagari Kapau. Imoroving risk management in reducing the risk of bad credit cannot be said to be running effectively and efficiently, whereas reducing the risk of fraud committed by employees is already running effectively.